RESEARCH OF THE STABILITY OF SCOPE BOARDS OF QUARRY BOARDS USING THE ENGINEERING METHOD - Urinov Sherali Raufovich; Askarov Agzam Muratovich; Mansurova Sevara Abdukarim kizi; Akhmedov Kahramon Abdukhailovich; Mirzakhmedov Muzaffar Bakhtiyorovich (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
An engineering method for calculating the stability of slopes in quarries is considered, the slope angles of high ledges and the height of sub-ledges are established when forming a concave slope profile of a high ledge.